2020
DOI: 10.1002/agj2.20364
|View full text |Cite
|
Sign up to set email alerts
|

Yield, persistence, forage nutritive value, and preference of perennial ryegrass under grazing

Abstract: Perennial ryegrass (PR) is a quality and high yielding forage that tends to lack winter hardiness to persist in the upper Midwest. The objective was to evaluate yield, stand persistence, forage nutritive value, and preference of experimental populations of winter hardy PR grown in monoculture and in mixture with white clover under livestock grazing. Research was conducted in St. Paul and Grand Rapids, MN. Meadow fescue (MF), tall fescue (TF), orchardgrass (OG), a reference PR, and two experimental populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Additionally, the forage processing protocols following sample collection can impact plant soluble carbohydrates ( Pelletier et al, 2010 ). In other equine grazing studies, summer NSC concentrations above 10% have been reported, particularly in perennial ryegrass [ Lolium perenne (L.)] pastures ( Allen et al, 2013 ; Grev et al, 2017 ; Catalano et al, 2020 ). It is possible that integrated grazing with Quick-N-Big CRB could aid in limiting NSC intake in pasture systems with different species composition and/or under alternative growing conditions.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, the forage processing protocols following sample collection can impact plant soluble carbohydrates ( Pelletier et al, 2010 ). In other equine grazing studies, summer NSC concentrations above 10% have been reported, particularly in perennial ryegrass [ Lolium perenne (L.)] pastures ( Allen et al, 2013 ; Grev et al, 2017 ; Catalano et al, 2020 ). It is possible that integrated grazing with Quick-N-Big CRB could aid in limiting NSC intake in pasture systems with different species composition and/or under alternative growing conditions.…”
Section: Resultsmentioning
confidence: 93%
“…Extrapolating data from studies in other livestock species is often of limited value in management decisions for horse operations ( Schmitz and Isselstein, 2020 ). Forage preference, grazing behaviors, nutritional requirements, digestive physiology, animal management goals, and drivers of enterprise profitability are vastly different ( NRC, 2007 ; Catalano et al, 2020 ; Schmitz and Isselstein, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to their turf‐type parentage, these populations are shorter in statue, which reduces their competitiveness with alfalfa. However, we expect these populations to be more tolerant to defoliation in grazing systems when paired with white clover ( Trifolium repens L.) (Catalano et al., 2020), where short stature is less of an impediment.…”
Section: Discussionmentioning
confidence: 99%